Review of Islamic Law on microtransaction contracts in the gacha system - Nur Rizqi Febriandika; Nurkholis Majid; Rahul Kumar (Universitas Muhammadiyah Magelang, 2022)
Gacha system is a game from Japan. The popularity of mobile games with a freemium (F2P) business model that uses the gacha system as a game monetization tool has become a problem when viewed from the legality of transactions according to Islamic law. Purchases of virtual items in the game are referred to as microtransactions, where players use real money that is spent into virtual items or game currency as a medium of exchange for these items. The freemium strategy has an attraction for players to spend money to explore a game. Gacha is a method to get virtual items in the game, the concept of gacha is very dependent on the probability and rarity of the item. The rarer the item, the player is required to spend more money. In Japan, in 2012, gacha was banned for carrying out a misleading campaign. This study aims to analyze the validity of the microtransaction contract system for purchasing virtual items using the gacha system according to Islam. This research uses the library research method. In collecting research data, the researchers analyzed sources from previous studies related to freemium business strategies, microtransactions and the use of the gacha system, as well as the rules of Islamic law from these various transactions. The results show that transactions using the gacha system contain elements of maysir, taghrir and tadlis. Using the gacha system without doing microtransactions with real money does not fulfil the elements of maysir, taghrir and tadlis. Meanwhile, players who perform microtransactions to buy in-game items directly or without going through gacha are included in the ijarah agreement. Players can also get rewards (sell) in the form of certain items if they grind as a gift from the game developer.